The Relationship Between Sleep Quality and the Risk of Type 2 Diabetes Among Nursing Students at the Sumedang Campus of the Indonesia University of Education - Adelia Gian Phalosa; Ahmad Purnama; Imam Tri Sutrisno (INDOGENIUS, 2026)
Background & Objective: Type 2 diabetes mellitus is a global health issue with a steadily rising prevalence, including in Indonesia. Sleep quality is recognized as a factor that may influence the risk of developing type 2 diabetes mellitus. However, research examining the relationship between sleep quality and the risk of type 2 diabetes mellitus in young adults, particularly college students, remains limited. This study aims to analyze the relationship between sleep quality and the risk of developing type 2 diabetes mellitus among students in the Nursing Program at the University of Education Indonesia, Sumedang Campus. Method: This study employed a quantitative approach with an analytical observational design and a cross-sectional method. The study population consisted of 446 students, with a sample size of 294 respondents who met the inclusion criteria. Data collection was conducted using the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality and the Finnish Diabetes Risk Score (FINDRISC) to measure the risk of type 2 diabetes mellitus. Data were analyzed using Spearman’s rho correlation test. Result: A total of 294 students aged 18–25 years participated in this study, with the majority of respondents being female. The analysis results showed that all respondents had poor sleep quality. Nevertheless, the majority of respondents were in the low-risk category for type 2 diabetes mellitus, totaling 242 individuals (82.31%). The results of the Spearman’s rho test showed no significant association between sleep quality and the risk of type 2 diabetes mellitus (p = 0.876; r = -0.009). Conclusion: There is no association between sleep quality and the risk of type 2 diabetes mellitus among nursing students. These findings suggest that, in the young adult age group, sleep quality is not a dominant factor influencing the risk of type 2 diabetes mellitus. Further research is recommended to examine other factors that may play a more significant role in the risk of type 2 diabetes mellitus.